Studies On Lipid Nutrition And The Expression Of Genes For Desaturase And Elongase Enzymes In Snakehead, Channa Striata (Bloch, 1793) Fingerlings - Paiko, Mohammed Aliyu (2011)

(untitled)
This study examined lipid nutrition in C. striata fingerlings, through a series of experimental feeding trials, including; the evaluation of lipid/protein ratio and fatty acid (FA) requirements, as well as the screening of some of its tissues for the expression of genes for fatty acyl desaturase (FAD) and fatty acyl elongase (FAE) enzymes. These preliminary studies provided some insight about lipid metabolism in the species; suggesting that snakehead fingerling requires 65/450 g kg